Use of artificial intelligence in the management of stroke: scoping review - Melo Sierra, Nicolas; Hernández Rincón, Erwin Hernando; Osorio Betancourt, Gabriela Alejandra; Ramos Chaparro, Paula Andrea; Diaz Quijano, Diana Marcela; Barbosa, Samuel David; Hernandez Restrepo, Michel; Uriza Sinisterra, Gustavo (Frontiers in Radiology, 2025)
IntroductionStroke is a condition that is more predominant in developed countries. However, it continues to be considered a high-cost health pathology worldwide, both in the medium and long term. Therefore, diagnosis, treatment, and rehabilitation are vital. Additionally, the assistance of artificial intelligence in these three principles has been increasing, given its effectiveness and efficiency in performance.ObjectiveThis study analyzes the available evidence regarding the use of artificial intelligence in primary care for stroke patients.MethodsA scoping review was conducted on three indexed databases, Science Direct, Web of Science, and PubMed, resulting in the identification of 1,382 articles. Initially, these terms were filtered on the basis of the year of publication and language. A second distinction was subsequently made through the title and abstract of each publication.ResultsA total of 33 articles summarizing 5 categories were selected: healthcare from a general point of view; stroke prediction; the diagnosis and treatment of both stroke and its sequelae; the risk of death in the poststroke period; and the assistance of AI in some specialties related to the disease.ConclusionArtificial intelligence has the potential to improve stroke care, but more research is still needed to evaluate its performance in clinical practice.IntroducciónEl accidente cerebrovascular es una condición predominante en los países desarrollados. A pesar de esto, es una patología de salud de alto costo en todo el mundo, tanto a mediano como a largo plazo. Por lo tanto, el diagnóstico, el tratamiento y la rehabilitación son de vital importancia. Por lo anterior, la asistencia de la inteligencia artificial en estos tres principios ha ido en aumento, dada su eficacia y eficiencia en el desempeño.ObjetivoEste estudio analiza la evidencia disponible sobre el uso de la Inteligencia Artificial en la atención primaria para el accidente cerebrovascular.MétodosSe realizó una revisión tipo Scoping Review en tres bases de datos indexadas: Science Direct, Web of Science y PubMed, lo que resultó en la identificación de 1,382 artículos. Inicialmente, estos se filtraron en función del año de publicación y el idioma. Posteriormente, se realizó una segunda distinción a través del título y el resumen de cada publicación.ResultadosSe seleccionaron un total de 33 artículos, que se seleccionaron en 5 categorías: atención médica desde un punto de vista general; predicción de accidente cerebrovascular; diagnóstico y tratamiento tanto del accidente cerebrovascular como de sus secuelas; riesgo de muerte en el período posterior al accidente cerebrovascular; y finalmente, la asistencia de la Inteligencia Artificial en algunas especialidades relacionadas con la enfermedad.ConclusiónLa Inteligencia Artificial tiene el potencial de mejorar la atención del accidente cerebrovascular, pero aún se necesitan más investigaciones para evaluar su desempeño en la práctica clínica.